Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction